Influences of a Pipeline's Bending Angle on the Propagation Law of Coal Dust Explosion Induced by Gas Explosion. Issue 5 (4th April 2021) - Zhang, Leilin; Yang, Qianyi; Shi, Biming; Niu, Yihui; Zhong, Zheng
ABSTRACT: A pipeline explosion system with different bending angles (45°, 60°, 90°, 120°, and 135°) was constructed to investigate the influences of the pipeline's bending angles on the propagation law of coal dust explosion induced by gas explosion. The change laws of the shock wave and flame after bending were analyzed. Results demonstrate that gas explosion can induce the explosion of deposited dust. After the explosion, the peak overpressure of the shock wave increases dramatically and then decreases slowly after the corner. The attenuation rate of the peak overpressure increases with the increase in the pipeline's bending angle. The flame propagation speed decreases first and then increases significantly after the corner. The change rate of flame propagation speed is positively related to the bending angle of pipelines. The flame front area presents a reverse V-shaped variation that greatly increases after the corner. Furthermore, the growth rate of the flame front area is positively related to the bending angle of pipelines.